ANSYS simulation for Ag/HEG Hybrid Nanofluid in Turbulent Circular Pipe - Tan, C.; Zainal, S.; Sian, C. J.; Siang, T. J. (Journal of Advanced Research in Applied Mechanics, 2020)
A CFD simulation analysis about enhancement of turbulent flow heat transfer in a horizontal circular pipe by convenient software where FLUENT was used to predict the heat transfer coefficient and Nusselt number for forced convection heat transfer of Ag/HEG+water nanofluid. The range of Reynolds number selected were 20 000 and 40 000 in a horizontal straight tube of diameter 0.01m with heat flux of 1000 W/m2. The volume fraction of nanoparticle considered were 0.1%, 0.2%, 0.3%, 0.5%, 0.7% and 0.9%. This problem also considered 100x30 meshing in order for Y+ to approach 1 to get more accurate results. The results show that the heat transfer coefficient and Nusselt number were decreasing with increasing of volume fraction. Finally, the results were compared with the theoretical values obtained from Dittus-Boelter Equation by using tool of package from ANSYSFLUENT which show similar results.